2013
DOI: 10.1111/mmi.12341
|View full text |Cite
|
Sign up to set email alerts
|

ICEA of Mycoplasma agalactiae: a new family of self‐transmissible integrative elements that confers conjugative properties to the recipient strain

Abstract: SummaryHorizontal gene transfer (HGT) is a major force of microbial evolution but was long thought to be marginal in mycoplasmas. In silico detection of exchanged regions and of loci encoding putative Integrative Conjugative Elements (ICE) in several mycoplasma genomes challenged this view, raising the prospect of these simple bacteria being able to conjugate. Using the model pathogen Mycoplasma agalactiae, we demonstrated for the first time that one of these elements, ICEA, is indeed self-transmissible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
130
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(135 citation statements)
references
References 47 publications
5
130
0
Order By: Relevance
“…For instance, the genome of M. agalactiae strain 5632 contains three almost identical copies of an entire ICE, ICEA 5632 , and two small regions (1.2 and 5.2 kbp, respectively) encoding ICE-related elements as remainders of past ICE insertions and decay (5,18). A vestigial ICE form displaying a reduced size and encompassing a large number of pseudogenes also occurs in M. agalactiae strain PG2 (vICEA PG2 ) (18) and was shown to be unable to transfer from cell to cell (19).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, the genome of M. agalactiae strain 5632 contains three almost identical copies of an entire ICE, ICEA 5632 , and two small regions (1.2 and 5.2 kbp, respectively) encoding ICE-related elements as remainders of past ICE insertions and decay (5,18). A vestigial ICE form displaying a reduced size and encompassing a large number of pseudogenes also occurs in M. agalactiae strain PG2 (vICEA PG2 ) (18) and was shown to be unable to transfer from cell to cell (19).…”
mentioning
confidence: 99%
“…It was then demonstrated that ICEA 5632 excision and integration are driven by a prokaryotic mutator-like transposase, a DDE transposase encoded by CDS22 of ICEA 5362 (19,21). Moreover, ICEA 5632 was shown to be self-transmissible and to disseminate horizontally from cell to cell via a conjugative process, with ICEA 5632 providing the recipient cell with the capacity to conjugate (19). Demonstration of ICEA 5632 trafficking in current mycoplasmas is an important step toward the understanding of HGT and of the contribution of ICE in this phenomenon.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…ICE6013 is now the third family of integrative conjugative elements, after TnGBS and ICEA (15,16), known to use a DDE Tpase as a recombinase and the first example to use the IS30 family of Tpases. While the prototypical IS30 element from E. coli carries a single ORF (36), the IS30-like Tpase from ICE6013 is encoded by two ORFs.…”
Section: Discussionmentioning
confidence: 99%
“…However, IS30-like Tpases acting as ICE recombinases have not yet been experimentally demonstrated. TnGBS from Streptococcus agalactiae and ICEA from Mycoplasma agalactiae are the only examples of ICEs demonstrated to use a Tpase as their recombinase (15,16); a Tpase from the p-MULT superfamily, which does not include IS30, is used for the excision of both elements (17).…”
mentioning
confidence: 99%